Expression of Intratumoral Forkhead Box Protein 3 in Posttransplant Lymphoproliferative Disorders. Issue 5 (May 2015) - Berglund, David; Kinch, Amelie; Edman, Elin; Backlin, Carin; Enblad, Gunilla; Larsson, Erik; Molin, Daniel; Pauksens, Karlis; Sundström, Christer; Baecklund, Eva
<x xml:space="preserve">Abstract</x> Background The infiltration of regulatory T cells (Tregs) in lymphomas is associated with better prognosis for some types of lymphomas, but knowledge of their role in posttransplant lymphoproliferative disorders (PTLDs) is limited. We therefore investigated the association between the expression of the Treg marker forkhead box protein 3 (FoxP3) in biopsies of PTLDs and survival, PTLD subtype, and clinical characteristics. Methods Seventy-four cases of PTLD after solid organ transplantation with sufficient material for further analysis were included from a population-based study of PTLDs in Sweden. The PTLD biopsies were reevaluated and stained with the 236A/E7 antibody to detect FoxP3 in lymphoma tissue. Detailed clinical data were collected retrospectively from medical records. Results Based on a cutoff level of 29 FoxP3+ cells per mm2, most (80%) of the PTLDs were FoxP3−. Forty-seven of 74 PTLDs displayed no FoxP3+ cells at all. The frequency of FoxP3+ cells did not influence median overall survival. The FoxP3− PTLDs were more frequently of T-cell phenotype (P = 0.04), located at the graft (P = 0.03), occurred earlier after transplantation (P = 0.04), were more likely to develop in lung recipients (P = 0.04), and in patients that had received anti–T-cell globulin as induction therapy (P = 0.02). The FoxP3+ PTLDs were associated with hepatitis C seropositivity (P = 0.03). In multivariate analysis, B-cell PTLD and hepatitis C infection were independent predictors of FoxP3 positivity. Conclusion Our findings suggest that intratumoral FoxP3+ Tregs do not influence survival in patients with PTLD. FoxP3+ Tregs are rare in PTLD, possibly because of heavy immunosuppression.